2015
DOI: 10.1039/c4nr07284g
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance supercapacitor of vertically-oriented few-layered graphene with high-density defects

Abstract: Pristine graphene with a 3D structure is desired for use in graphene-based supercapacitors, yet the very poor wettability of such graphene in water has limited its practical application. Here we report a way to simultaneously realize the 3D structure and good wettability in vertically-oriented few-layered graphene (VFG) grown by plasma-enhanced chemical vapor deposition. Based on scanning and transmission electron microscopic, Raman spectroscopic, contact angle (CA) and electrochemical analyses, a mechanism to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…discharge time in GCD curves, which may be due to the fact that transport of the electrolyte ion cannot be fully carried out at a low current density (Figure 5C). This phenomenon stems from the nature of the gel electrolyte and the inherent properties of the material (Qi et al, 2015;Wang P. et al, 2018). When the current density is 10 A·g −1 , a high C sp of 106.3 F·g −1 can be delivered, which shows a retention of 88.1% (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…discharge time in GCD curves, which may be due to the fact that transport of the electrolyte ion cannot be fully carried out at a low current density (Figure 5C). This phenomenon stems from the nature of the gel electrolyte and the inherent properties of the material (Qi et al, 2015;Wang P. et al, 2018). When the current density is 10 A·g −1 , a high C sp of 106.3 F·g −1 can be delivered, which shows a retention of 88.1% (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…Each Raman spectra of VGs contained four prominent bands at $1340 cm À1 , $1590 cm À1 , $2685 cm À1 , $2935 cm À1 , respectively, which were closed to the typical spectra of carbon materials. 31,44 The intensity ratios of I D /I G were calculated as 2.81, 2.74, and 2.72 for DC-VGs, ICP-VGs, and MW-VGs, respectively, suggesting similar defects level and disorder in the sp 2 graphene structure. 13,44 On the other hand, the I 2D /I G ratios of DC-VGs, ICP-VGs, and MW-VGs were 0.46, 0.67, and 0.88, respectively, indicating the multi-layer graphenes in VG nanosheets.…”
Section: Morphology and Microstructure Of Vgsmentioning
confidence: 96%
“…21 Feng's group revealed that the wettability of VGs could be controlled from hydrophobic to hydrophilic nature by introducing different densities of defects. 19,31 In fact, the resulting apparent wettability of VGs is determined by the interplay between the capillary force arising from the wetting of VG walls and the repulsion from the compressed air. Consequently, an investigation on the dependence of the wettability of VGs and an understanding on the liquid electrolyte permeation inside VG interiors are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 5 (d) http://engine.scichina.com/doi/10.1016/j.jechem.2017.11.014 rapidly, indicating the good electrochemical reversibility [43,44] . According to Eq.…”
Section: Electrochemical Performances Of Asymmetric Supercapacitor Ofmentioning
confidence: 99%
“…In the impedance spectra, the starting point intersecting with the X-axis in the high frequency region is series resistance ( R S ) caused mainly by the conductive substrate, connecting wires and contact resistance. The diameter of the semicircle represents the charge transfer resistance ( R CT ) at the electrode/electrolyte interface, curve slope in the low frequency region represents the diffusion-limited processes ( Z w ), respectively [31,[38][39][40][41][42][43][44] . Fig.…”
Section: Electrochemical Performances Of Comoo 4 /Co 1 −X S Electrodementioning
confidence: 99%